Respuestas
Respuesta dada por:
1
A) X (
) = ![\frac{-36}{6} \frac{-36}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B-36%7D%7B6%7D+)
![\frac{3x}{5} = \frac{-6}{y} \frac{3x}{5} = \frac{-6}{y}](https://tex.z-dn.net/?f=+%5Cfrac%7B3x%7D%7B5%7D+%3D++%5Cfrac%7B-6%7D%7By%7D+)
3X = - 30
X =![\frac{- 30}{3} \frac{- 30}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B-+30%7D%7B3%7D+)
X= - 10
B) X (
) = ![\frac{2}{3} \frac{2}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B3%7D+)
![\frac{5x}{4} = \frac{2}{3} \frac{5x}{4} = \frac{2}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B5x%7D%7B4%7D+%3D++%5Cfrac%7B2%7D%7B3%7D+)
15X = 8
X =![\frac{8}{15} \frac{8}{15}](https://tex.z-dn.net/?f=+%5Cfrac%7B8%7D%7B15%7D+)
C) 2X =![\frac{- 5}{3} \frac{- 5}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B-+5%7D%7B3%7D+)
6X = - 5
X =
3X = - 30
X =
X= - 10
B) X (
15X = 8
X =
C) 2X =
6X = - 5
X =
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años